Influence of aging and hemorrhage injury on Sirt1 expression: Possible role of myc-Sirt1 regulation in mitochondrial function - Jian, Bixi (2011)
Trauma-hemorrhage (T-H) causes hypoxia and organ dysfunction. Mitochondrial dysfunction is a major factor for cellular injury due to T-H. Aging also has been known to cause progressive mitochondrial dysfunction. In order to study the effect of aging on T-H-induced mitochondrial dysfunction, we recently developed a rodent mitochondrial genechip with probesets representing mitochondrial and nuclear genes contributing to mitochondrial structure and function. Using this chip we recently identified signature mitochondrial genes altered following T-H in 6 and 22 month old rats; augmented expression of the transcription factor c-myc was the most pronounced. Based on reports of c-myc-IL6 collaboration and c-myc-Sirt1 negative regulation, we further investigated the expression of these regulatory factors with respect to aging and injury. Rats of ages 6 and 22 months were subjected to T-H or sham operation and left ventricular tissues were tested for cytosolic cytochrome c, mtDNA content, Sirt1 and mitochondrial biogenesis factors Foxo1, Ppara and Nrf-1. We observed increased cardiac cytosolic cytochrome c (sham vs T-H, p<0.03), decreased mitochondrial DNA content (sham vs T-H, p<0.05), and decreased Sirt1 expression (sham vs TH, p<0.05) following T-H and with progressing age. Additionally, expression of mitochondrial biogenesis regulating transcription factors Foxo1 and Nrf-1 were also decreased with T-H and aging. Based upon these observations we conclude that Sirt1 expression is negatively modulated by T-H causing downregulation of mitochondrial biogenesis. Thus, induction of Sirt1 is likely to produce salutary effects following T-H induced injury and hence, Sirt1 may be a potential molecular target for translational research in injury resolution.